Gender differences in models of using the Internet and social adaptation of children and youth - Juza, Szymon; Nogas, Beata (Studia Psychologica: Theoria et praxis, 2011)
The main goal of our research is to show how boys and girls differ in using the Internet. We raise this problem in the context of Internet Addiction Syndrome and face it with social adaptation at school. This question gains a practical character, because answering it allows us to form guidelines for all who cope with psycho-prophylactics of the young generation. Main conclusion of our research shows a characteristic way of Internet usage by each gender which is reflected in the way one is addicted to the Internet. These dependences are not so clear at 11-13, but get really visible at 14-16 years. Generally, there are no differences in the level of Internet addiction between genders. High level of that syndrome and specific models of using the Internet coexist with some dimensions of social maladjustment. Please see the main text for a more detailed analysis.